A Temporal Perspective of Merger and Acquisition and Strategic Alliance Initiatives - Shi, Weilei (Stone); Sun, Jing; Prescott, John E. (Journal of Management, 2012)
The incorporation of a temporal perspective in merger and acquisition (M&A) and alliance research has gained increasing popularity. Since a temporal perspective focuses on the management of time and its consequences, it contributes a unique value proposition to the M&A and alliance stream of research. Over the past 30 years researchers have explored a wide variety of topics and methodological approaches. As a result, research evidence has progressed in a somewhat fragmented manner where its cumulative impact is difficult to discern. The purpose of this review is to systematically assess the underlying logic and contributions of a temporal lens for the M&A and alliance literature as well as identify core temporal constructs, mechanisms, relationships, and promising research directions. The authors’ review of 144 published articles not only catalogs the state of the art and accumulated knowledge but also identifies critical hurdles that need to be addressed to chart future research directions.